Patient experience of health care system hassles: Dual‐system vs single‐system users. (7th May 2020) - Noël, Polly H.; Barnard, Jenny M.; Barry, Frances M.; Simon, Alissa; Lee, Martin L.; Olmos‐Ochoa, Tanya T.; Chawla, Neetu; Rose, Danielle E.; Stockdale, Susan E.; Finley, Erin P.; Penney, Lauren S.; Ganz, David A.
Abstract: Objective: To compare health care system problems or "hassles" experienced by Veterans receiving VA health care only versus those receiving dual care from both VA and non‐VA community providers. Data Sources: We collected survey data in 2017‐2018 from 2444 randomly selected Veterans with four or more primary care visits in the prior year at one of 12 VA primary care clinics located in four geographically diverse regions of the United States. Study Design: We used baseline surveys from the Coordination Toolkit and Coaching quality improvement project to explore Veterans' experience of hassles (dependent variable), source of health care, self‐rated physical and mental health, and sociodemographics. Data Collection: Participants responded to mailed surveys by mail, telephone, or online. Principal Findings: The number of reported hassles ranged from 0 to 16; 79 percent of Veterans reported experiencing one or more hassles. Controlling for sociodemographic characteristics and self‐rated physical and mental health, zero‐inflated negative binominal regression indicated that dual care users experienced more hassles than VA‐only users (adjusted predicted average 5.5 [CI: 5.2, 5.8] vs 4.3 [CI: 4.1, 4.6] hassles [ P < .0001]). Conclusions: Anticipated increases in Veterans accessing community‐based care may require new strategies to help VA primary care teams optimize care coordination for dual care users.